2020
DOI: 10.20473/jde.v5i2.19447
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization in Indonesian Cooperatives: Is It Necessary?

Abstract: Digitalization has already penetrated all sectors of life and dominates business models. This study evaluates the extent to which small businesses should adopt digitalization. We focus on the cooperative's business model currently fighting with another fast-growing and popular business model, the start-up. Then, we used direct field research, including descriptive analysis and in-depth interviews with cooperatives in the Yogyakarta Special Region, Indonesia. We found that that the use of digital media by coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
2
Order By: Relevance
“…One of the key forces behind MSMEs' sustained competitive advantage is innovation. Several experts assert that the use of digital technology is necessary to improve the productivity and performance of SMEs (Nurdany & Prajasari, 2020;Papadopoulos et al, 2020). Digital technology can support the performance of MSMEs during this large-scale social restriction period.…”
Section: H 1 : Access To Financing Has a Positive And Significant Eff...mentioning
confidence: 99%
“…One of the key forces behind MSMEs' sustained competitive advantage is innovation. Several experts assert that the use of digital technology is necessary to improve the productivity and performance of SMEs (Nurdany & Prajasari, 2020;Papadopoulos et al, 2020). Digital technology can support the performance of MSMEs during this large-scale social restriction period.…”
Section: H 1 : Access To Financing Has a Positive And Significant Eff...mentioning
confidence: 99%
“…UMKM masih minim yang berplatform digital (Adhinegara, 2020). Hal ini diperkuat penelitian Nurdany & Prajasari bahwa penggunaan media digital koperasi masih minim (Nurdany & Prajasari, 2020). Berdasarkan data tersebut dihubungkan dengan data peneliti menunjukkan bahwa koperasi masih minim menggunakan platform digital.…”
Section: Pendahuluanunclassified
“…Berdasarkan data tersebut dihubungkan dengan data peneliti menunjukkan bahwa koperasi masih minim menggunakan platform digital. Hal ini karena sejumlah koperasi tetap mempertahankan non-digital karena kurangnya preferensi (Nurdany & Prajasari, 2020). Selain itu, peneliti melihat bahwa ada kecemasan koperasi dalam menerapkan teknologi yang dianggap "eksklusif" dan informasi negatif terkait beberapa kasus platform digital.…”
Section: Pendahuluanunclassified
“…12 In delivering this research, the researcher conducted a research mapping to position this research on research distinction and novelty. The study by Achmad Nurdany and Anniza Citra Prajasari (2020) found that using digital media by cooperatives has not been widely used. 13 Research by Purbasari et al (2022) found that the digital transformation of cooperatives in the Greater Bandung area is good but still needs improvement.…”
Section: Introductionmentioning
confidence: 99%